The relationship between sleep disorders and frailty in stroke patients: the mediating role of self-efficacy - Niu, Shuyuan; Liu, Manjiang; Lin, Yingjie; Gu, Peiqi; Zhao, Li (Frontiers in Psychiatry, 2025)
BackgroundStroke patients may have symptoms such as sleep disorders, and the incidence of frailty is much higher than that of non-stroke patients. Self-efficacy can reduce the occurrence of frailty and sleep disorders and help to maintain the health of stroke patients.ObjectiveTo investigate the relationship between sleep disorder, self-efficacy and frailty in stroke patients, and to analyse the mediating role of self-efficacy.MethodsThis study was a cross-sectional study, and 6 “stroke map” sites were selected in Shenyang from June to September 2024. A total of 924 stroke patients were included, and a structural equation model (SEM) was constructed to analyse the mediating effect of self-efficacy on sleep disorders, self-efficacy and frailty in stroke patients.ResultsThe prevalence of debilitation in stroke patients was 46.2%. Sleep disorders were positively correlated with frailty (P<0.01) and negatively correlated with self-efficacy. Self-efficacy is negatively correlated with frailty, which is the intermediary between sleep disorders and frailty.ConclusionThe prevalence of frailty in stroke patients is high. Sleep disorders are highly correlated with frailty, and self-efficacy plays a mediating role between sleep disorders and frailty, which can reduce the impact of sleep disorders on frailty development.